Distributional Effects of Tax Reforms in Japan : Micro-simulation Approach - Hisanaga, Takuma (IMF Working Papers; Working Paper, 2022)
This paper conducts micro-simulations to study the distributional effects of several tax measures in Japan, considering households' heterogeneity in terms of both income and wealth. Simulation results suggest that increasing the consumption tax rate and strengthening the recurrent tax on immovable property would weigh more heavily on low-income households with large wealth than on those of comparable incomes with small wealth, and that introduction of a consumption tax credit would be effective in containing a rise in tax burden of low-income households.